2020
DOI: 10.18502/jfrh.v13i4.2648
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Rapid Biophysical Profile in Comparison to Biophysical Profile in Pregnant Women with Insulin-dependent Diabetes

Abstract: Objective: Having a rapid and low cost diagnostic approach in assessment of fetal wellbeing is an important goal for prenatal care process. The aim of this study was to determine the diagnostic value of rapid biophysical profile (rBPP) in comparison to biophysical profile (BPP). Materials and methods: In this study 142 pregnant women with insulin-dependent diabetes referred to Besat Hospital (Sanandaj, Iran) were evaluated in terms of fetal health. Age, gestational age and non-stress test (NST) data of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Accorddingly, the sensitivity and specificity of rBPP were 56.2% and 90.5% respectively. Researchers concluded that rBPP method compared to MBPP has a better capacity to discriminate non-distressed fetuses from distressexposed fetuses and they recommended its use as a quick and easy method in crowded centers with limited evaluation tests [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Accorddingly, the sensitivity and specificity of rBPP were 56.2% and 90.5% respectively. Researchers concluded that rBPP method compared to MBPP has a better capacity to discriminate non-distressed fetuses from distressexposed fetuses and they recommended its use as a quick and easy method in crowded centers with limited evaluation tests [24] .…”
Section: Discussionmentioning
confidence: 99%
“…3 In that study, the authors noted that intrauterine death was preceded by reduction in perception of fetal movements in the previous 3-4 days, followed by complete cessation of perception of the movements 12-48 hours before eventual fetal demise. 3 Soufizadeh et al 4 also reported that while RFM was a predictor of adverse fetal outcomes, perception of normal movements is especially useful to the mother as it allays fears of imminent fetal death. For the obstetrician, it offers assurance of good fetal wellbeing in case postponement of delivery is needed to allow for lung maturity.…”
Section: Introductionmentioning
confidence: 99%
“…For the obstetrician, it offers assurance of good fetal wellbeing in case postponement of delivery is needed to allow for lung maturity. 4 For the expectant female, RFM is a major cause of concern. Consequently, reduced fetal movements have been shown to be a major indication for hospitalisation, at the detriment of overwhelming the facilities, and crucially, especially in the third world, the already low numbers of the healthcare workers.…”
Section: Introductionmentioning
confidence: 99%